Mesenchymal Stromal Cell-Derived Extracellular Vesicles Restore Thymic Architecture and T Cell Function Disrupted by Neonatal Hyperoxia - Reis, Monica; Willis, Gareth R.; Fernandez-Gonzalez, Angeles; Yeung, Vincent; Taglauer, Elizabeth; Magaletta, Margaret; Parsons, Teagan; Derr, Alan; Liu, Xianlan; Maehr, Rene; Kourembanas, Stella; Mitsialis, S. Alex (Frontiers in Immunology, 2021)
Treating premature infants with high oxygen is a routine intervention in the context of neonatal intensive care. Unfortunately, the increase in survival rates is associated with various detrimental sequalae of hyperoxia exposure, most notably bronchopulmonary dysplasia (BPD), a disease of disrupted lung development. The effects of high oxygen exposure on other developing organs of the infant, as well as the possible impact such disrupted development may have on later life remain poorly understood. Using a neonatal mouse model to investigate the effects of hyperoxia on the immature immune system we observed a dramatic involution of the thymic medulla, and this lesion was associated with disrupted FoxP3+ regulatory T cell generation and T cell autoreactivity. Significantly, administration of mesenchymal stem/stromal cell extracellular vesicles (MEx) restored thymic medullary architecture and physiological thymocyte profiles. Using single cell transcriptomics, we further demonstrated preferential impact of MEx treatment on the thymic medullary antigen presentation axis, as evidenced by enrichment of antigen presentation and antioxidative-stress related genes in dendritic cells (DCs) and medullary epithelial cells (mTECs). Our study demonstrates that MEx treatment represents a promising restorative therapeutic approach for oxygen-induced thymic injury, thus promoting normal development of both central tolerance and adaptive immunity